1981
DOI: 10.1055/s-2007-1019377
|View full text |Cite
|
Sign up to set email alerts
|

Muscle LPL Activity, Plasma and Muscle Triglycerides in Trained Thyroidectomized Rats

Abstract: A training-induced increase in muscle LPL activity was found only in euthyroid animals. However, muscle LPL activity is already elevated in non-exercised thyroid-deficient rats. Training caused similar or greater decreases in muscle and plasma TG levels in hypothyroid as compared to euthyroid animals. These data indicate that training-induced changes in TG metabolism are not dependent on an euthyroid status and suggest that a hypothyroid status may enhance TG utilization during exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
1

Year Published

1984
1984
2005
2005

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
1
6
1
1
Order By: Relevance
“…Data are mean ± SD ES Effect size (difference between means divided by the SD of the untrained group); MUFA monounsaturated fatty acids; PUFA polyunsaturated fatty acids; ND not detected; U/S unsaturated/ saturated; UI unsaturation index *Significantly different from untrained (P<0.05) a Indices of enzyme activity were calculated from the sum of the concentration of each fatty acid in PL and TG Concerning muscle, its total TG content was greatly reduced with training. Most of the relevant studies have found decreases (Froberg et al 1972;Kaciuba-Uscilko et al 1981;Oscai et al 1982), although no differences between trained and untrained rats have also been reported (Lee et al 2002). The reduction found in the present study (by 75%) was larger than the ones found in the soleus (32%) and EDL (34%) of the same animals , suggesting a greater responsiveness of gastrocnemius muscle TG to training.…”
Section: Discussioncontrasting
confidence: 75%
“…Data are mean ± SD ES Effect size (difference between means divided by the SD of the untrained group); MUFA monounsaturated fatty acids; PUFA polyunsaturated fatty acids; ND not detected; U/S unsaturated/ saturated; UI unsaturation index *Significantly different from untrained (P<0.05) a Indices of enzyme activity were calculated from the sum of the concentration of each fatty acid in PL and TG Concerning muscle, its total TG content was greatly reduced with training. Most of the relevant studies have found decreases (Froberg et al 1972;Kaciuba-Uscilko et al 1981;Oscai et al 1982), although no differences between trained and untrained rats have also been reported (Lee et al 2002). The reduction found in the present study (by 75%) was larger than the ones found in the soleus (32%) and EDL (34%) of the same animals , suggesting a greater responsiveness of gastrocnemius muscle TG to training.…”
Section: Discussioncontrasting
confidence: 75%
“…In contrast, Hurley and co-workers (132) failed to observe a significant change in the triacylglycerol content of the vastus lateralis muscle in male subjects after a strenuous training program for 12 weeks, confirming earlier findings (85). Moreover, in rats the content of triacylglycerols was found to be decreased in fasttwitch red, slow-twitch red, and fast-twitch white fibers after endurance training (143,200). At present, no satisfactory explanation for the deviating findings can be offered (98).…”
Section: Utilization Of Intramuscular Triacylg/ycerols In Endurance-tmentioning
confidence: 38%
“…In the same muscle, hyperthyroidism causes a decrease in LPL activity. The observation that sequestration of radiolabeled fatty acids, derived from circulating triacylglycerols, in red muscle cells is increased in the hyperthyroid animals led the authors to conclude that an inverse relationship exists between LPL activity and circulating triacylglycerol utilization in cases of high levels of plasma thyroid hormones (143).…”
Section: Fatty Acids In Circulating Lipoproteinsmentioning
confidence: 98%
See 1 more Smart Citation
“…In the rat, training has been shown to reduce the content of TG in each muscle type (FroÈ berg 1969;Kaciuba-Us ciøko et al 1981;Oscai et al 1982). In the present study, training reduced the TG content in the soleus muscle and the diaphragm and did not aect their content in either sections of the gastrocnemius muscles.…”
Section: Discussionmentioning
confidence: 99%